Investigation of the Effect of Fin Geometry on the Thermal Performance of Microelectronics Devices - Yaseen, Sana J.; Hadi, Ali K.; Abed, Ali A.; Sharkawy, Abdel-Nasser (Engineering Transactions, 2026)
This study systematically evaluates optimal heat sink geometry for enhanced thermal performance in electronic cooling applications. ANSYS-Icepak and COMSOL Multiphysics software assessed four distinct fin geometries (square, rectangular, circular, and conical), all uniformly sized for accurate comparison. Vital performance parameters were analyzed, including maximum temperature reduction, pressure drop, and airflow velocity. These indicators provide a holistic assessment of cooling efficacy and aerodynamic characteristics. Findings highlight the effectiveness of rectangular fins, which significantly reduce maximum temperatures due to their efficient balance of conductive and convective heat transfer. While conical fins display lower pressure drops and circular fins achieve higher airflow velocities, these attributes do not consistently enhance cooling capabilities. The importance of this study resides in its provision of definitive guidance for selecting fin geometry in designing efficient heat sinks, crucial for electronic devices. This knowledge is particularly vital for developing advanced cooling systems in compact, high-power electronics, underscoring the significant impact of fin geometry on overall thermal management efficiency. Quantitative data supporting these findings is available in the full study.